Sensuality in perfume advertisements: an analysis of multimodality in Cosmopolitan and Cosmopolitan Men magazine - Jatrifia Ongga Sinatrya (UPT P2M Politeknik Negeri Malang, 2016)
This paper studies about sensuality in advertising, focusing on qualitative research and content analysis using the theory of multimodality as a reference. This study focuses on the perfume advertising that appeared in Cosmopolitan and Cosmopolitan Men, Indonesian edition of June, September, December 2013 and March 2014.The results of data analysis showed that the perfume ads in Cosmopolitan and Cosmopolitan Men Indonesia show the element of sensuality and sexuality. The use of female models in perfume advertising for women aims to encourage Indonesian women to change just as western models that exist in the perfume ads in Cosmopolitan Indonesia magazines and changing the beauty standards of Indonesian women. Men consumers no longer embarrassed to imagine about male models in perfume advertisements and want a body looks like the male model; it is what we called male erotic imagination. Cultural shift also occurs; perfume advertisements in Cosmopolitan and Cosmopolitan Men bring cultural modernization in Indonesia, where sensuality and sexuality is no longer a taboo for women and men in Indonesia.